STUDY ON ANTIOXIDANT AND CYTOTOXIC PROPERTIES OF OLEA DIOICA ROXB. CRUDE EXTRACT AND ITS PURE COMPOUND COLLECTED FROM WESTERN GHATS, KARNATAKA, INDIA. - ASHWATHANARAYANA R; RAJA NAIKA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Introduction: Olea dioica Roxb. an important medicinal tree plants used by local siddha tribes, belongs to the family Oleaceae. The parts such as leaves, bark, root, and fruits used in the traditional medicine to cure skin diseases, rheumatism, fever, and cancer. Objectives: The anti-oxidant experiment by metal chelating activity, superoxide radicals, hydroxyl radical, 2,2-diphenyl-2-picrylhydrazyl radicals, 2,2-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid radical scavenging assays with in vitro cytotoxicity was tested using trypan blue dye exclusion technique and 3-(4, 5 dimethylthiazole-2yl)-2, 5-diphenyltetrazolium bromide assay was conducted. Results: Anti-oxidant experiments revealed that the bark ethanolic extract of the O. dioica plant parts has excellent radical scavenging activity and its extracted pure compound, Benzene ethanol, 4-hydroxy-alcohol, showed excellent radical scavenging activity higher than the standards used. In vitrocytotoxicity experiments revealed that bark ethanolic extract has excellent cytotoxicity activity and its pure compound benzene-ethanol, 4-hydroxyalcoholalso showed excellentactivitywhichis comparablewith the standardcurcumin. Conclusion: O. dioica bark could be exploited as a valuable source of antioxidant and cytotoxic agent for pharmaceutical industry. Keywords: Olea dioica Roxb, Metal chelating, Superoxide radicals, Hydroxyl radical, 2,2-diphenyl-2-picrylhydrazyl radicals, 2,2-azinobis(3-ethylbenzothiazoline)-6-sulfonic acid radical scavenging,Trypan blue, 3-(4,5dimethylthiazole-2yl)-2, 5-diphenyltetrazolium bromide assay, Benzeneethanol, 4-hydroxy-alcohol.